2018
DOI: 10.3390/fluids3030064
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Validation of a Free Open Source 1D Water Hammer Code

Abstract: This paper presents a free code for calculating 1D hydraulic transients in liquid-filled piping. The transient of focus is the Water Hammer phenomenon which may arise due to e.g., sudden valve closure, pump start/stop etc. The method of solution of the system of partial differential equations given by the continuity and momentum balance is the Method of Characteristics (MOC). Various friction models ranging from steady-state and quasi steady-state to unsteady friction models including Convolution Based models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Brunone and Vítkovský's friction models have been implemented by different authors who reported similar results of high accuracy than the previously implemented friction models [22,23,33]. Vardy and Brown's model provided the best damping and wave attenuation results compared to the previously mentioned models [22]. This is attributed to the high accuracy of the convolutional-based unsteady friction models.…”
Section: Comparison Of Friction Modelsmentioning
confidence: 86%
See 4 more Smart Citations
“…Brunone and Vítkovský's friction models have been implemented by different authors who reported similar results of high accuracy than the previously implemented friction models [22,23,33]. Vardy and Brown's model provided the best damping and wave attenuation results compared to the previously mentioned models [22]. This is attributed to the high accuracy of the convolutional-based unsteady friction models.…”
Section: Comparison Of Friction Modelsmentioning
confidence: 86%
“…Vítkovský's model provides slightly more accurate results than Brunone's as it has the sign correction term [32]. Brunone and Vítkovský's friction models have been implemented by different authors who reported similar results of high accuracy than the previously implemented friction models [22,23,33]. Vardy and Brown's model provided the best damping and wave attenuation results compared to the previously mentioned models [22].…”
Section: Comparison Of Friction Modelsmentioning
confidence: 99%
See 3 more Smart Citations